2002
DOI: 10.1161/01.cir.0000043022.44032.77
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Flow Velocity Pattern Immediately After Percutaneous Coronary Intervention as a Predictor of Complications and In-Hospital Survival After Acute Myocardial Infarction

Abstract: Background— Recently, it was reported that the degree of microvascular injury and left ventricular functional recovery during the chronic period can be predicted after treatment of the infarct-related artery based on the coronary flow velocity (CFV) pattern assessed using a Doppler guidewire. The aim of this prospective study was to examine whether the CFV pattern may predict complications and in-hospital survival after acute myocardial infarction (AMI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…12,15 More recently, the CFV pattern was found to be an accurate predictor of in-hospital complications and survival after AMI. 11 Here, we show that both in-hospital and long-term adverse clinical events can be predicted by the CFV pattern both qualitatively and quantitatively immediately after primary or rescue PTCA, establishing a relationship between the risk of adverse clinical events and microcirculatory function measured by intracoronary Doppler examination.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…12,15 More recently, the CFV pattern was found to be an accurate predictor of in-hospital complications and survival after AMI. 11 Here, we show that both in-hospital and long-term adverse clinical events can be predicted by the CFV pattern both qualitatively and quantitatively immediately after primary or rescue PTCA, establishing a relationship between the risk of adverse clinical events and microcirculatory function measured by intracoronary Doppler examination.…”
Section: Discussionsupporting
confidence: 52%
“…However, microvascular injury is determined not only by the size of the infarct but also by reperfusion injury, 16 PTCA-induced thrombus, and atheroma fragmentation. 17 Indeed, patients with severe microvascular injury immediately after PTCA have a higher frequency of ST-segment re-elevation 11 or incomplete ST-segment resolution, 18 and a continuously declining post-PTCA velocity has been linked to vessel reocclusion. 19 Several studies have shown that patients with no reflow on myocardial contrast echocardiography 20 or Doppler guidewire assessment 9,11,12 have poor functional LV recovery and a high frequency of complications such as CHF, pericardial effusion, cardiac tamponade, and cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The attenuated CFR response post PCI seems to be associated with future cardiovascular events. 22 Recently, several studies have tested other invasive indexes in comparison with CFR, e.g., index of microvascular resistance and hyperemic microvascular resistance index, pointing out promising data about reproducibility and prognostic value. 23,24 All together, these insights from clinical pathophysiology could support therapeutic approaches beyond the primary PCI procedure itself.…”
Section: Invasive Indexes Of Coronary Microvascular Obstructionmentioning
confidence: 99%